Prevalence of Tactile Hallucination of Phone Vibration among Individuals Aged 18–22 Years - Tanisha Sunil Mali; Trupti Yadav (Indian Journal of Psychiatric Nursing)
Background: Overuse of phones can lead to physiological health hazards. The repeated use of vibration mode leads to fake perception of device being vibrating when it is not. Tactile hallucination of phone vibration is a prevalent phenomenon among young individuals. Theories explaining the possibility of the phenomenon are proven through researchers. Design: The study was a cross-sectional survey in design. Participants: Two hundred and four individuals responded to the questionnaire. Material and Methods: An electronic survey consisting of 12 questions based on demographic, mobile usage hours, and frequency of phantom vibrations experienced. An online questionnaire was used for the study. It is known as the Phantom Vibration Scale or phantom vibration questionnaire which was taken from an article (reference 9). The questionnaire was formed on Google Forms application and was circulated on WhatsApp in the form of a link through a smartphone. It consisted of 11 questions. The questions were brief and are easy to understand as it is supposed to cover a large population. The population selected was healthy without any neurological or psychological problem. The questionnaire consisted of questions on the duration of phone usage in a day, to know the risk of tactile hallucination in them. It had questions on whether they experience tactile hallucinations and information about its frequency and intensity. Results: Two hundred and four responses were received, out of that 68% experienced tactile hallucinations. Those who experienced hallucinations, were further observed for different characteristics presented. Nearly 88% possessed a smartphone for more than a year. Respondents were asked about the phone usage hours and the majority used it for 3–5 h daily. Social media are a known addiction of phone and the survey showed that 55% of the respondents used phones to scroll social media. The next factor which is vibration mode of the phone was used by 17% of the people always. About 29% used it for most of the time. About the placement, while carrying of phone, it showed that 69% always carried phone in their jean front pocket. Furthermore, 42% of the participants found those vibrations to be bothersome. Nearly 21% had the hallucinations so severe that they felt it when the phone was switched off. Conclusions: More than half of the people on this planet carry smartphone and most use it on vibration mode. Even if one-third of them experience hallucinations, a planned treatment is required for this.